Use of Melatonin in Oxidative Stress Related Neonatal Diseases - Gabriella D'Angelo; Roberto Chimenz; Russel J. Reiter; Eloisa Gitto (MDPI AG, 2020)
Reactive oxygen species have a crucial role in the pathogenesis of perinatal diseases. Exposure to inflammation, infections, or high oxygen concentrations is frequent in preterm infants, who have high free iron levels that enhance toxic radical generation and diminish antioxidant defense. The peculiar susceptibility of newborns to oxidative stress supports the prophylactic use of melatonin in preventing or decreasing oxidative stress-mediated diseases. Melatonin, an effective direct free-radical scavenger, easily diffuses through biological membranes and exerts pleiotropic activity everywhere. Multiple investigations have assessed the effectiveness of melatonin to reduce the "oxygen radical diseases of newborn" including perinatal brain injury, sepsis, chronic lung disease (CLD), and necrotizing enterocolitis (NEC). Further studies are still awaited to test melatonin activity during perinatal period.